Pensamiento educativo de N. K. Krupskaya - Javier Ninahuaman, Henry Juan (2022)
The study of qualitative approach, descriptive of narrative and analytical design of topics, deals with the thought in the pedagogical field of the biggest representative of the Russian Education, N. K. Krupskaya, and makes an analysis of the factors that intervened for his Marxist approach. It also shows historically the development of her life and ideology together with her greatest achievements for which she is recognized worldwide. It aims to describe his pedagogical thought and the factors intervening in his formation after diligently systematizing the data collected in the register, they are categorized and structured taking into account the synthetic analysis by triangulation of texts.  It makes a description of their identification, the principles of the unique school, free or Soviet as well as the omnilaterality development as the desired characteristic in the students of this pedagogy, together with their methods and the combination that makes of the work with the education and their intervention in the orphanages and the feminism that are being revaluated in this time, on the other hand some experiences of their thought and inheritance are shown. She concludes by characterizing her as the greatest female representative of Russian pedagogy that puts the collective before individuality, a fruitful author of publications and the creator of the single, free or socialist school.